PENGARUH E MODUL DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA PELAJARAN SBDP DI SEKOLAH DASAR - Kanthi Asri; Eka Titi Andaryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The focus of this research is on the problem of conventional learning, characterized by low student learning outcomes in SBDP and a lack of motivation to learn. Therefore, a new learning approach is needed to increase students' desire to learn. The development of the e-module aims to increase students' motivation to learn. The research subjects consisted of one subject matter expert, one instructional design expert, one learning media expert, three students who participated in individual trials, and nine students who participated in small group trials. Data was collected through observation, interviews, and questionnaires. Data analysis was conducted through qualitative and quantitative descriptive analysis. The results of the research show that the developed e-module is valid with the following evaluations: content expert evaluation (94.23%), design expert evaluation (92.3%), media expert evaluation (86%), individual trial evaluation (91.53%), and small group trial evaluation (90.62%). Thus, it can be concluded that the use of the e-module can increase students' desire to learn SBDP in fourth grade.